MODEL PENANAMAN KEDISIPLINAN ANAK USIA DINI PADA KELUARGA BURUH WANITA DI DESA BAKREJO KECAMATAN SUKOHARJO KABUPATEN SUKOHARJO - Gunairiyah, Meirina (Jurusan PGPAUD FIP UNNES, 2013)
Discipline needs to be invested since the child was a child as a way to help children to develop self- control. Educating children with discipline as the efforts of parents to guide children towards better behavior, so that children have the awareness and behave autonomously moral obedience comes from within the child. Moral values derived from the pattern of family life (father and mother) as the ideal model for imitation and identification of the child's behavior and self-identification through habituation. The purpose of this study was to: 1) determine the model of early childhood investment discipline, 2) determine differences in perspective investment discipline to children between the mother and the father. The subjects in this study were kindergarten children aged 4-6 years, parents and teachers work as laborers. Data collection techniques used observation, interview and documentation. Data analysis with data reduction, data display, and conclusion drawing and verification. The results showed that the model of early childhood investment discipline on women workers in the Village District Bakrejo Sukoharjo Sukoharjo includes models authoritarian, permissive and democratic. There is a difference of view between the child's investment discipline to mothers with fathers, mothers tend to use positive discipline approach while fathers tend to use negative discipline approach. It can be concluded that the environment in which a child grows and grew up going to affect the child's development process